Okun's Law across time and frequencies - Aguiar-Conraria, Luís (2020)
We present the first assessment of U.S. Okun's Law across time and frequencies. We use a set of continuous wavelet tools that allows for estimating Okun's coefficient and the lead/lag of output over unemployment at each moment and for each cyclical frequency. We find similar results for the gaps and the first differences specifications at business cycles frequencies, but not at lower frequencies. Okun's coefficient has increased (in absolute value) since the mid-1960s, except in 1985-1995, and is not particularly sensitive to recessions. The lead of output varies considerably over time and also at different frequencies. We observe (especially with the gaps specification) that there are at least two cyclical processes relevant for the Okun's relationship, one at the business cycle and another at lower frequencies. Methods that do not take this into account are bound to mix the information embedded in both cycles.